LEKSIKON-LEKSIKON FLORA DALAM METAFORA BAHASA BALI: KAJIAN EKOLINGUISTIK - I Made Astu Mahayana; Ni Ketut Sukiani; Ni Made Suwendri; Made Detrichyeni Winaya (Universitas Warmadewa, 2019)
[Title: Lexicons of Flora in Balinese Metaphors: Ecolinguistic Studies]This research is an ecolinguistic study focused on metaphors that is related to ecological environment that concerns flora. The reseacrch is firstly aimed at finding and analyzing the lexicons of flora found in Balinese metaphors. Secondly, it is aimed at analyzing and describing cognitive metaphorical meaning between the source and target, and thirdly is aimed at analyzing and describing how the metaphors and metaphorical expressions were constructed. The method used in this research was descriptive qualitative method. The written data were collected from some sources, like Basita Parihasa (book collection of words, sarcasms, metaphors, and others in Balinese), a short story of Balinese containing metaphorical expressions and a Balinese song lyric. The spoken data were collected from an informan as a native speaker of Balinese language.Based on the analysis results, The metaphorical meanings found in this writing mostly showed the similarity, such as body shape, characteristic, situation, and conditon of a human. In other words, cognitive process occured by conceptualizing bodily experience by similarity of the source and target domain in processing metaphorical expressions. It is also found that the Balinese metaphors were constructed by mapping process through ecolinguistic parameters. The mapping process occured, due to the similarity of character or system between source and target, especially Balinese people and ecological environment (flora which exist in Bali). The metaphors were also constructed by bodily experience of the language users which were recorded in human’s cognitive under the praxis social dimension.